Crystal phase control in GaAs nanowires: opposing trends in the Ga- and As-limited growth regimes. (10th July 2015) - Lehmann, Sebastian; Jacobsson, Daniel; Dick, Kimberly A
Abstract: Here we demonstrate the existence of two distinct regimes for tuning crystal structure in GaAs nanowires from zinc blende to wurtzite using a single process parameter: V/III-ratio, or variation of the group V precursor flow. Extensive previous studies have shown that crystal structure is sensitive to V/III-ratio, and even that it is possible to change structure entirely using this single parameter. However, an open question has remained about whether the observed dependencies are related to growth technique or types of precursors used. Specifically, opposite trends have been reported for molecular beam epitaxy (MBE) and metal organic vapour phase epitaxy (MOVPE): while wurtzite GaAs growth is reported for high nominal V/III-ratio in MBE, zinc blende GaAs is formed in MOVPE under apparently the same parameter change (increasing precursor V/III-ratio). Here we show that these observations are not necessarily contradictory, as it may first appear, by providing a consolidated picture covering all regimes in one MOVPE growth machine only. More precisely, we observe wurtzite formation for medium nominal V/III-ratios with a critical sensitivity to the balance between Ga and As supply. Slight deviations from wurtzite conditions will result in zinc blende formation for either low V/III-ratio in the As-limited regime or high V/III-ratio in the Ga-limited regime. Our observations strongly indicate that the applied growth conditions are the crucial ingredients for crystal structure control in GaAs nanowires rather than the growth technique or precursors used.